Handbook of self-regulation - Boekaerts, Monique; Pintrich, Paul R.; Zeidner, Moshe (Elsevier Academic Press, 2005)
Provides an overview of a relatively new and increasingly important area in psychological research: self-regulation. The range of topics covered by the chapters in this handbook include the use of self-regulation constructs in various areas of psychology, such as social, personality, clinical, developmental, educational, organizational, health, and community psychology. The 23 chapters are organized into three sections: (1) general theories and models of self-regulation that can be applied to many different domains of human behavior; (2) domain-specific applications of self-regulation theory and research in the areas of educational, health, and organizational psychology; and (3) application of self-regulation constructs to improve practice. The concluding chapter presents 12 general themes or overlapping issues the field of self-regulation must consider in future theory and research.